2013
DOI: 10.1021/ie4029544
|View full text |Cite
|
Sign up to set email alerts
|

UltraHigh Molecular Weight Nonlinear Polycarbonates Synthesized in Microlayers

Abstract: Ultrahigh molecular weight bisphenol A polycarbonate (BPAPC) with nonlinear chain structures has been synthesized by solid-state polymerization in microlayers at 230°C. It has been found that the molecular weights of the microlayers of low molecular weight prepolymers with thickness ranging from 5 to 35 μm increased rapidly to ultrahigh molecular weight (300,000−600,000 g/mol) without any discoloration. The amorphous prepolymers exhibited much higher reaction rate than the partially crystallized prepolymers. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…[10] The typical PC process is composed of a transesterification and a polycondensation stage. [11][12][13] In the transesterification stage, DPC and BPA monomers are initially polymerized to form a low molecular weight prepolymer with a basic catalyst in stirred reactor. Then, the prepolymer is further polymerized to obtain the high molecular weight PC at higher temperature (250-300 °C) during the finishing polymerization stage.…”
Section: Doi: 101002/mren201700042mentioning
confidence: 99%
See 1 more Smart Citation
“…[10] The typical PC process is composed of a transesterification and a polycondensation stage. [11][12][13] In the transesterification stage, DPC and BPA monomers are initially polymerized to form a low molecular weight prepolymer with a basic catalyst in stirred reactor. Then, the prepolymer is further polymerized to obtain the high molecular weight PC at higher temperature (250-300 °C) during the finishing polymerization stage.…”
Section: Doi: 101002/mren201700042mentioning
confidence: 99%
“…The typical PC process is composed of a transesterification and a polycondensation stage . In the transesterification stage, DPC and BPA monomers are initially polymerized to form a low molecular weight prepolymer with a basic catalyst in stirred reactor.…”
Section: Introductionmentioning
confidence: 99%
“…But the molecular weight decreased as the crystallinity increased above 39.5%. Higher crystallinity could decrease SSP rate by inhibiting the mobility of polymer chains in the amorphous phase and hindering the diffusion of by‐product throughout the polymer particles . As a result of crystallinity effect, BAPC prepolymer of 2 h crystallization time with crystallinity of 37.1% synthesized the highest molecular weight of 57,343 in SSP reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In the solid‐state polymerization of BPAPC in amorphous micro‐layers (SSP m ), the reaction byproduct (phenol) can be removed more effectively than in micro‐particles and hence high molecular weight is obtained in short reaction time . A small amount of casting solvent left in the micro‐layer can also act as a plasticizer to facilitate the movement of chain segments at the reaction temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical modeling of a single SSP particle used in such conventional SSP process has shown that significant diffusion resistance is present in the transport of phenol (byproduct of polycondensation of BPAPC) from the particle interior to the external surface of the particle . In our recent work, we have reported that when BPAPC is polymerized in thin micro‐layers under solid‐state polymerization conditions, very high molecular weight polycarbonate ( M w > 100,000 g mol −1 ) can be obtained in short reaction time …”
Section: Introductionmentioning
confidence: 99%